Detecting the Diversity of Mycoplasma and Ureaplasma Endosymbionts Hosted by Trichomonas vaginalis Isolates - Ioannidis, Anastasios; Papaioannou, Panagiota; Magiorkinis, Emmanouil; Magana, Maria; Ioannidou, Vasiliki; Tzanetou, Konstantina; Burriel, Angeliki R.; Tsironi, Maria; Chatzipanagiotou, Stylianos (Frontiers in Microbiology, 2017)
Objectives: The symbiosis of Trichomonas vaginalis and Mycoplasma hominis is the first described association between two obligate human parasites. Trichomonas is the niche and the vector for the transmission of M. hominis infection. This clinically significant symbiosis may affect T. vaginalis virulence and susceptibility to treatment. The aims of this study were to investigate the intracellularly present Mycoplasma and Ureaplasma species in T. vaginalis strains isolated from the vaginal discharge of infected women as well as to trace the diversity pattern among the species detected in the isolated strains. Methods: 100 pure T. vaginalis cultures were isolated from approximately 7.500 patient specimens presented with clinical purulent vaginitis. PCR and sequencing for Mycoplasma/Ureaplasma spp. were performed in DNA extracted from the pure cultures. In addition, vaginal discharge samples were cultured for the presence of M. hominis and U. urealyticum. Phylogenetic analysis assisted the identification of interspecies relationships between the Mycoplasma and Ureaplasma isolates. Results: 54% of T. vaginalis isolates were harboring Mycoplasma spp. Phylogenetic analysis revealed three distinct clusters, two with already characterized M. hominis and Ureaplasma spp. (37.04% of total Mycoplasma spp.), whereas one group formed a distinct cluster matched with the newly identified species Candidatus Mycoplasma girerdii (59.26%) and one or more unknown Mycoplasma spp. (3.70%). Conclusions: T. vaginalis strains associated with profound vaginal infection frequently host intracellular mycoplasmas or ureaplasmas, belonging to species that remain undetected in the extracellular environment when conventional diagnostic methods are implemented. Intracellular mycoplasmas or ureaplasmas may comprise either novel species, such as Candidatus M. giredii, or unknown species with yet unexplored clinical significance.